Multi-Criteria Decision Making (MCDM) for bachelor of aircraft engineering technology (avionic) final year students in project management course: AHP method for career selection - Mohammad, M.F. (Medwell Journals, 2017)
Career selection for many especially for students is a crucial process. Previous studies show that job seeker chose career either based on income, academic qualification or the benefit that may gain. This study was conducted among final year BAET students taking project management course at Universiti Kuala Lumpur Malaysian Institute of Aviation Technology (UniKL MIAT) to identify MCDM used by students in selecting a career. Students are distributed into small groups (between four to five members). Contrary to other earlier studies-whereby a list of criteria and scale range used for criteria are given, this study allowed students to figure out the list of criteria and scale range to be used for comparison based on their discussion within their own group. Students were also allowed to set their own range of scale for comparing the criteria and alternatives. The criteria were then analyzed using Analytical Hierarchy Process (AHP) method to identify the chosen career by students. The highest score among each group was then taken to check on its consistencies to ensure the alignment of the scoring with the objective of AHP method which is to provide objective and minimize subjective decision criteria. Apart from understanding the MCDM used by students in selecting a career, AHP method exercise in the class as part of the tutorial for project management course has helped students to understand the decision-making process using AHP. © Medwell Journals, 2017.